The Incidence of Pregnancy-Associated Cushing's Disease and Its Relation to Pregnancy: A Retrospective Study - Tang, Keyun; Lu, Lin; Feng, Ming; Zhang, Hanlin; Chen, Kang; Sun, Xu; Zhu, Huijuan; Wang, Renzhi; Lu, Zhaolin (Frontiers in Endocrinology, 2020)
Purpose Cushing’s disease (CD) is one of the most severe endocrine disorders and primarily affects women of reproductive age. The peripartum period has been observed to be a common time to develop CD. This study aims to retrospectively analyze the clinical characteristics of CD potentially associated with pregnancy and to evaluate relevant pregnancy outcomes. Methods Patients who underwent surgery from January 2010 to May 2019 at Peking Union Medical College Hospital (PUMCH) with biochemically and pathologically confirmed CD were retrospectively analyzed. Pregnancy-associated CD was defined as CD onset during gestation or within 12 months after delivery or abortion. Data including demographics, biochemical tests, magnetic resonance imaging (MRI) findings, and disease outcomes were obtained from all patients by reviewing their medical records. Information regarding pregnancy was collected through a supplementary online questionnaire. Results In a series of female patients (n=70) of reproductive age with childbearing desire, 27.1% (n=19) met the criteria for pregnancy-associated CD. The timing of diagnosis of pregnancy-associated CD was 2.7 ± 3.4 years after symptom onset, and the overall remission rate for these women was 89.5%. Three patients with pregnancy-associated CD developed hypertension during pregnancy, two of whom had new-onset hypertension at 16 weeks of gestation and one of whom had a complication of severe diabetes. The rates of spontaneous abortion and preterm birth among the women with pregnancy-associated CD were 26.3% and 28.6%, respectively. The proportions of all low-birth-weight (LBW) newborns (p=0.002) and term LBW newborns (p=0.033) were significantly higher in the pregnancy-associated CD group than in the non-pregnancy-associated CD group. Conclusions In this study, a total of 27.1% of women of reproductive age with CD had pregnancy-associated CD, which might be induced by the hormonal milieu of pregnancy. An increased risk of having a LBW newborn was observed among mothers with pregnancy associated CD. A high degree of clinical suspicion for CD may be warranted in the peripartum period. Patients with symptoms suspicious for CD throughout pregnancy and after childbirth, such as early-onset hypertension, severe hyperglycemia, and persistent weight gain, should be carefully diagnosed and closely monitored by clinicians.